(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: The use of grayscale ultrasound with Doppler mea¬surements allows the experienced sonogra¬pher to reliably diagnose functional, benign, and malignant adnexal masses. Information obtained from pelvic ultrasound, with the patient’s history and gynecologic exam, guides recommendations for treatment, mainly the decision for conservative follow-up or surgery.The Ovarian-Adnexal Reporting and Data System (O-RADS) US risk stratification and management system provide consistent interpretations to eliminate ambiguity in US reports which results in a higher probability of accuracy in the assessment 0f risk of malignancy to ovarian and other adnexal masses and also to provide a management recommendation for each risk category. This study aimed to evaluate the Importance of using the O-RADS classification system US in the diagnosis of suspicious ovarian mass lesions. The O-RADS US classification system must help the healthcare provider decide which lesions require no follow-up or conservative follow-up, also with the aid of a US specialist for optimal characterization, versus lesions that require consultation with a gynecologist or gynecologic oncologist